Hubungan Antara Self-Esteem dan Adversity Quotient Dengan Kemandirian Belajar pada Siswa Sekolah Menengah Pertama - Djauhari, Dodik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract,The Purpose of this study is to determine the relationship between the Self-Direction Learning with Self Esteem, and the relationship the Self-Direction Learning with Adversity Quotient, separately or simultaneously. Variables used in this study consists of the independent variables , the Self-Esteem (X1), Adversity Quotient (X2). While the dependent variable, is the Self-Direction in Learning (Y). The subject of this study are goverment junior high school 4 Gresik students class VIII. The Analysisresult state that Self-Esteem correlated positively with Self-Direction Learning . But Adversity Quotient is positively correlated with Self-Direction Learning . This means that significant, the variable Self-Esteem and Adversity Quotient togetherly affect significantly to the Independence of Learning. Keywords: Self-Esteem, Adversity Quotient, Self-Direction Learning